ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI NILAI EKSPOR PERHIASAN KE BEBERAPA NEGARA DI DUNIA TAHUN 2014 - 2018 - Piani, Ni Made Okta; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 5 (2021): VOL 10 NO 5, MEI 2021 (1774 - 2222), 2021)
The development of the Fashion World in Indonesia is happening very rapidly due to globalization and supporting media. Most people in Indonesia think that Fashion or Style is everything. Fashion has become a necessity for most Indonesian people. The value of exports of finished clothes is indicated to occur because of the level of market demand from the destination countries of export of finished clothes to Indonesia. The purpose of this study is (1) to analyze the influence of the US dollar exchange rate, inflation and production rates simultaneously on apparel exports in Indonesia and (2) to analyze the influence the US dollar exchange rate, inflation and production levels are partially of apparel exports in Indonesia. The data used are secondary data obtained from the publication of the Central Statistics Agency. The analysis technique used is multiple linear regression analysis. The software used is SPSS 23. The results show that the dollar exchange rate, inflation, and production simultaneously affect the export of Indonesian apparel. The dollar exchange rate has a positive but not significant effect on Indonesian apparel exports. Inflation has a positive but not significant effect on Indonesian apparel exports. Production has a positive and significant effect on Indonesian apparel exports. Keywords : Dollar Exchange Rate, Inflation, Production, Export of Apparel